Ethnicity, security, and separatism in India - Chadda, Maya (Oxford University Press, 1997)
Ethnicity, Security, and Separatism in India examines the connections between internal and external policy and the ways in which domestic ethnic conflicts shape a state's international security perceptions and policies. Chadda focuses on three ethnonationalisms and their international dimensions: Kashmir and Punjab in India-Pakistan relations and the Tamil issue in India-Sri Lanka relations.